News Framing on Malay Deli Culture in medan.tribunnews.com Online Media - Rudianto, Rudianto; Anshori, Akhyar (Universitas Muhammadiyah Yogyakarta, 2020)
This article aims to analyze how the frame of online media coverage in Medan on Malay Culture. The identity of Ethnic Malay Culture in Medan can be found in several buildings that become icons of Medan city such as Maimon Palace and Masjid Raya Al Mahsun located in the center of Medan City. In addition to having various icons related to Malay, Medan is also a city with native Malay people. Along with the stream of globalization, Malay Culture is increasingly widely recognized by the community or public through the mass media, mainly online media in Medan. This research was conducted through a qualitative approach with a constructivist paradigm through Entman framing model analysis method. The results of this article are that the online media in Medan in this case www.medan.tribunnews.com gives a wide space in spreading Malay Culture in Medan. Three findings are related to the reporting themes, government and community involvement in the preservation and attractiveness of Malay Culture depicted in the news is a hope that the Malay culture will be maintained and sustainable in the community of the city of Medan despite the stream of globalization.